Two Different Poles Of Disagreeing Strategies In Indonesian Graduate EFL Discussions - Zuliati Rohmah (Universitas Negeri Malang, 2016)
The present study is concerned with verbal strategies applied by doctorate students in expressing their disagreements during discussions in English as a Foreign Language (EFL) classes. The study collected data from fourteen classroom discussions among the doctorate English Program students speaking in English as a foreign language. Among the five broad strategies applied, aggravating a disagreement seems to be an undesired strategy, and, acknowledging peers and asserting vulnerability during disagreements are the more favored strategies. Hence, the results of the study strengthen Viechnicki's (1997) findings that intellectual figure is fundamental to the graduate students that needs to be protected